Tips for Integrating Land and Wildlife Management: Deer in Ranchlands - William M. Giuliano; John M. Olson; Cailey Thomas (EDIS)
In addition to having generally low-quality foods, ranchlands often have a low diversity of food sources, further reducing the quality of habitat for deer. Ranchland management for deer should therefore focus on providing a diversity of abundant, high-quality foods. This 2-page fact sheet provides some deer habitat improvement tips that focus primarily on raising the quality of deer forage but that also will help you grow better cover by improving plant diversity and productivity. Written by William M. Giuliano, John M. Olson, and Cailey Thomas, and published by the UF Department of Wildlife Ecology and Conservation, January 2013.